Comprehensive characterization reveals antimicrobial-resistant and potentially virulent Campylobacter isolates from poultry meat products in Southern Brazil. (September 2021) - Würfel, Simone de Fátima Rauber; Prates, Denise da Fontoura; Kleinubing, Natalie Rauber; Vecchia, Joline Dalla; Vaniel, Cristiane; Haubert, Louise; Dellagostin, Odir Antônio; Silva, Wladimir Padilha da
Abstract: The aim of this study was to perform a comprehensive characterization of 48 Campylobacter isolates obtained from broiler meat products in Southern Brazil, which had been previously typed by pulsed-field gel electrophoresis (PFGE). The antimicrobial resistance (AMR) profile and the presence of 30 virulence-associated genes (VAGs) were investigated. Six AMR patterns and 26 VAG patterns were found, indicating a great genetic diversity among the isolates. It is noteworthy that 79.2% of Campylobacter isolates were resistant to one or more antimicrobial agents, and MDR was found in 35.4%, being more prevalent in C. jejuni isolates. Data analysis for the combination of AMR and VAG profiles indicated that the antimicrobial resistance and virulence profile were not related to a particular species. The combination of the PFGE, AMR and VAG sets of data improved the discrimination power. In addition, the presence of antimicrobial-resistant Campylobacter isolates carrying virulence genes such as hcp (T6SS marker), cgtB and wlaN (LOS biosynthesis markers), among others, represents a potential emerging threat to public health. The findings also demonstrate the need for more rigorous control measures for Campylobacter in the Brazilian poultry production chain to avoid the dissemination of antimicrobial resistant and virulent Campylobacter isolates through the poultry meat. Highlights: The highest levels of resistance were observed to tetracycline. Multidrug resistance was found in 35.4% of the Campylobacter spp. isolates. Six AMR patterns and 26 VAG patterns were identified in the isolates. The antimicrobial resistance was not related to a particular species of C. jejuni or C. coli . The combination of the PFGE, AMR and VAG sets of data improved the discrimination among the isolates.